Transplantação hepática por hepatocarcinoma Experiência nacional - Marques, Hugo Pinto (2007)
Background: Results of liver transplantation for hepatocellular carcinoma are comparable to those of liver transplantation for other diseases. Although it is commonly done in the various liver transplant Centres in Portugal , until now no study analyzed the global results of this therapeutic strategy in our Country. Objectives: To evaluate the global results of liver transplantation for hepatocellular carcinoma in Portugal . Patients and Methods: Between 1993 and 2006, 137 patients were submitted to liver transplantation for hepatocellular carcinoma. There were 122 men and 15 women. Most frequent aetiologies were cirrhosis due to alcohol, HCV and HBV. Forty-seven patients were submitted to preoperative therapy, most frequently transarterial chemoembolization. The median size of the largest nodule was 4,3 cm and 16 patients had more than three nodules. Eighty patients fulfilled Milan Criteria and 95 patients fulfilled University of California – San Francisco (UCSF) Criteria. Kaplan-Meier and Log Rank tests were used for statistical analysis. Results: Operative mortality was 13,1% (18 patients). Twenty-seven patients (19,7%) relapsed, most frequently in the lung or liver. Overall 5-year survival was 56%, and 10-year survival was 32%. Patients fulfilling Milan Criteria had a 73% 5-year survival. Patients fulfilling UCSF Criteria had a 72% 5-year survival. The most important factors influencing survival were number and size of nodules, as well as the presence of vascular invasion. Conclusion: In Portugal, liver transplantation for hepatocellular carcinoma respecting standard selection criteria achieves results that are equivalent to most international series. Expansion of those criteria obtained satisfactory results in our Centres.